The Effect Of ESP Courses On Students' Achievement Of Coherence In General Academic Writing Tasks - Khorsheed, ranwa (ELT-Lectura, 2025)
It has been observed that when students do writing tasks on general topics in English, their writings tend to have a poor content and weak coherence. On the other hand, when students do writing tasks on ESP topics, their writings tend to exhibit a good coherence , a rich content and a variety in the use of jargon based vocabulary. The purpose of this study is to help students produce cohesive and coherent English texts by integrating their ESP writing skills with those of general English writing skills.